Implementation of the West Java Anti-Thuggery Task Force Policy from a Socio-Legal and Good Governance Perspective - Mochammad Rifky Setiawan; Dimas Aryo Yuwono; Jepryanto Yehezkiel; Relby Alexandra (LPPM Universitas Harapan Bangsa, 2026)
This study examines the contradictions between the administrative mandate of West Java Governor Decree No. 300/Kep.160-Bakesbangpol/2025 establishing the Anti-Thuggery Task Force and the persistent sociopolitical reality of protection rackets. Employing a socio-legal approach grounded in legal realism, the research analyzes law in action through triangulation of in-depth interviews with academics and mass organization leaders and field analysis of violent incidents, particularly the Sukahaji case. The findings demonstrate that although the policy enhances visibility management and administrative surveillance through smart city technologies, it fails to dismantle entrenched structural patronage relations. A “paradox of protection” emerges, whereby formal state presence inadvertently normalizes informal coercive power over citizens, while the legally imprecise collective labeling of mass organizations fosters defensive solidarity and increases the risk of secondary deviance. This study contributes a novel critique of regional “statification” technologies that privilege performative order over substantive justice and argues that the Task Force must be transformed into a non-discriminatory law enforcement mechanism, integrated with inclusive economic empowerment and anchored within a democratic legal framework.